EP activity evaluation of cyclic disulphides using ball bearings of different compositions - Bhattacharya A.; Singh T.; Verma V.K. (My University, 2025)
Employing a four-ball machine and using steel ball bearing specimens of 12.7 mm diameter, the potential EP activity of certain cyclic disulphide additives in liquid paraffin has been evaluated. The additive (3,5-di-p-Cl-phenylimino-1,2,4-dithiazolidine) has a comparatively good ISL value (100 kgf), higher values of weld load (> 500 kgf), mean Hertz load and FTP, and lower values of wear scar diameter and coefficient of friction. It appears to show excellent anti-friction properties and has been found to be effective with ball bearings of different compositions. The topography of the ball bearing surface was studied by using the technique of scanning electron microscopy. © 1990.